How to dance. A complete ball-room and party guide. Containing all the latest figures, together with old-fashioned and contra dances now in general use. Also, a guide to ballroom etiquette, toilets, and general useful information for dancers. (New York, Tousey & Small, 1878)
Designed for people who never learned to dance either because of bashfulness or lack of time or money, this manual covers the bare necessities of dress, introductions, and general etiquette. Descriptions are also provided for the quadrille, schottisch, polka redowa, waltz, and several country dances. The manual concludes with rules for the supper room and advice to waltzers.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Dance -- Handbooks, manuals, etc; Country dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals